Post-conflict reconstruction : from extremism to peaceful co-existence - Sulaiman, Sadia (Thousand Oaks, California : SAGE Publications Inc, 2020)
"Post-Conflict Reconstruction: From Extremism to Peaceful Co-Existence is a comprehensive presentation on the root causes of state fragility, which provides an enabling environment for violent religious extremism. It addresses various security, political, socio-economic and external factors that contribute to state fragility, which is further enhanced in a conflict environment. The book deals closely with the use of violence due to ideological, religious and political reasons. By analyzing the situations in the post-conflict states of Afghanistan, Iraq, Yemen, Pakistan, Nigeria and Libya, the book establishes the co-relationship between state fragility and religious extremism in post-conflict settings. The book emphasizes the need to address the grievances of marginalized sections in all countries with fragile state structures that usually take to violence to make their voices heard. It also highlights the imperative for swift rehabilitation of poor people-who typically bear the brunt of conflicts and are often displaced forcefully-for restoring peace and security, and averting future disturbance"--
Introduction -- Post-conflict reconstruction, state fragility and extremism: Connnecting the missing dots -- State fragility and extremism in post-Taliban Afghanistan -- State fragility and the rise of ISIS in Iraq -- Yemen: Walking on a tight rope to avert extemism -- Pakistan: Caught btween fragility and extremism trap -- Perfect blending of fragility with extremism: Nigeria -- Post-conflict fragility and road to extremism in Libya.
Includes bibliographical references (pages [229]-251) and index.
Keywords: Peace-building.; Peace-building -- Social aspects; Postwar reconstruction; Political stability; Radicalism; Religious fanaticism